2022
DOI: 10.1038/s41524-022-00895-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of ultrafast X-ray induced magnetization dynamics in magnetic multilayer systems

Abstract: In this work, we report on modeling results obtained with our recently developed simulation tool enabling nanoscopic description of electronic processes in X-ray irradiated ferromagnetic materials. With this tool, we have studied the response of Co/Pt multilayer system irradiated by an ultrafast extreme ultraviolet pulse at the M-edge of Co (photon energy ~60 eV). It was previously investigated experimentally at the FERMI free-electron-laser facility, using the magnetic small-angle X-ray scattering technique. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…For comparison, the density of states for fcc bulk Co (with 25 ) used in Refs. 6 , 7 is also presented. The calculated magnetic moments of nickel and cobalt are and , respectively, i.e., with a good agreement with those from 9 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For comparison, the density of states for fcc bulk Co (with 25 ) used in Refs. 6 , 7 is also presented. The calculated magnetic moments of nickel and cobalt are and , respectively, i.e., with a good agreement with those from 9 .…”
Section: Resultsmentioning
confidence: 99%
“…This X-ray induced electronic excitation changes the population of spin-up and spin-down electrons in the band. As the electronic occupation in the d -band determines the magnetization of the material, this results in the decrease of the total magnetic moment in the material 6 – 8 . In our previous studies 6 , 7 , we modeled the experimentally observed ultrafast decrease of magnetic small-angle X-ray scattering (mSAXS) signal from X-ray irradiated cobalt which reflected a transient decrease of the cobalt magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations